STUDY OF DIGITAL SERVICE TRANSFORMATION IN FINANCIAL TRANSACTIONS AT RAJA AHMAD TABIB HOSPITAL WITH SWOT ANALYSIS APPROACH - Kristina Harahap; Erisna Dewi Ariyani; Andri Saputra; Susilo Budi Hartanto; Sepyenita; Syarifah Fatimah; Indrayani; Muammar Khaddafi; Jumadil Saputra (PT. Radja Intercontinental Publishing, 2023)
In the existence of digital transformation in the field of health services in order to improve it. So that the Raja Ahmad Tabib of Regional Public Hospital has implemented a Hospital Management Information System (SIM-RS) which is integrated with the Quick Response Indonesian Standard (QRIS) as a tool for using digital transactions as a method of payment in cashier service products that are more transparent and accountable so that services for patients are more efficient and effective. Therefore, this study aims to identify the strengths, weaknesses, opportunities and threats to the transformation of digital services in financial transactions. Based on the SWOT analysis mapping, a strategy that is very suitable for the position of Raja Ahmad Tabib Hospital, namely the SO strategy (Comparative Advantage Strategy).